Práticas discursivas maternas e compreensão de estados mentais: um estudo com crianças de 3 anos e 6 meses a 4 anos - Oliveira, Fernanda Germani de (2009)
The present paper report investigates the hypothesis of an association between the language experiences of a child has along family environment (here also considering influence from kindergarten school) and the development of a mental state comprehension. This experiment questions what effects an intervention program with mothers, which aims to orient them to use mental state explanatory language (their own mental state and others) causes on a mind theory development on children from 3,6 years old to 4 years old, both boys and girls. The research occurred in two local kindergarten schools from Itajaí city (SC). About 40 motherschild pairs participated in the study where 20 of them were the experimental group (GE) and the others 20 pairs were the control group (GC). This almost-experimental research type was divided into three parts: a) Pre-test: the five first tasks from the mind theory study of Wellman and Liu (2004) studies were applied to the children and only the ones who did not reached the right answers to the fifth question of false believe attribution participated in the study. The mothers were asked to tell a story to their child participating on the research. b) Experimental intervention aiming to orient the mothers to use verbs and other mental terms to narrate stories which consisted of characters mental state attribution and comprehension, including desire, intention and others believes attribution. The training lasted four sessions, one session a week. Mothers from the control group were guided to narrate the same stories with no specific orientation of how to do it. Each week the researcher met the mother for an interview about the instructions given on the previous week. The mother was told to keep the book story during a week and she was oriented to try a verbal interaction with her child, repeating the same story always emphasizing mental states c) Post-Test: after a week from the intervention, the children were evaluated using the same five tasks from mind theory study. Again, the mothers were asked to tell the child a story, using the same book story previously used in the pre-test phase. The results presented that language causes a strong effect on the development of mind theory in children and on the experimental group these effects were significantly more present where mothers were asked to use verbs and other mental terms. Post-test phase showed that children from both groups (GE) and (GC) made progress on mental state comprehension however children from (GE) did it better especially on the false believe task. Therefore, these results support the hypotheses that lead to an existence of a relation between the ability to attribute mental state and language development. It also leads for the fact that conversation between mother-child pairs made it possible to develop the ability of comprehending and attributing mental but the use of mental terms on purpose the way it was done on the (GE), sure causes more effect and benefits the performance in false believe tasks